Environmental impact assessment of aseptically packaged chicken using ohmic heating - Ito, Ruri; Yamanaka-Zamoto, Noriko; Watanabe, Manabu; Hamada-Sato, Naoko (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2023)
We evaluated the environmental impact of aseptically packaged chicken using ohmic heating. Ohmic heating is a method that directly applies electric power to food. CO2 emissions were determined for each stage and compared with retort-heated food products. Retort-heated foods were assumed to be packaged by two methods: retort pouches and canned food. Replacing cans with pouches reduced CO2 emissions by 64 %. CO2 emissions were reduced by more than 80 % by replacing retort heating with ohmic heating. Additionally, the characterized results of 13 environmental areas indicate that the substitution of canned foods with aseptically packaged foods using ohmic heating can potentially reduce the environmental impact by up to 88 %. Furthermore, in the quality evaluation, ohmic-heated foods retained the same or better quality and palatability as the retort-heated foods. Aseptically packaged food products using ohmic heating can be substituted for conventional retort heating methods to reduce the environmental impact without sacrificing palatability.